GEOLOGICAL POSITION OF ALKALINE SODIUM METASOMATITE FORMATION OF NOVOUKRAINKA MASSIF - MYKHALCHENKO, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The expediency of separation of independent alkaline sodium metasomatite formation of paleoproterozoic within the region is proved.